Mastitis in a Holstein x Sahiwal cow caused by streptomycin-resistant Pasteurella multocida - Manzanilla, Russel Denny O. (The Philippine Journal of Veterinary Medicine, 2021)
Mastitis, the most economically relevant disease in the dairy industry, can be caused by a wide array of bacterial species. Although scarcely reported, Pasteurella multocida is included as a contagious etiologic agent causing mastitis. Targeting the pathogens is the treatment approach when dealing with udder infection and with bacteria being the chief causative agents, antibiotics is prominently utilized for therapy. This dairy farm was previously treating its mastitis cases using a Penicillin-Streptomycin solution for intramuscular injection without veterinary supervision. The collection of milk samples from infected quarters was prompted by non-response of their mastitis cases to antibiotic treatment. The selection of quarters for sample collection was based on the severity of clinical signs present. Bacterial isolation was performed using the milk samples afterward, the isolated bacteria, Staphylococcus aureus and P. multocida, were subjected to antibiotic sensitivity tests. The two isolates shared a resistance against streptomycin, an antibiotic previously used in the farm in combination with benzylpenicillin. Thus, a different antimicrobial drug, oxytetracycline, was prescribed to which the pathogens responded positively.